PENERAPAN LEAN HOSPITAL DALAM MENINGKATKAN PELAYANAN GAWAT DARURAT DI RUMAH SAKIT: LITERATURE REVIEW - Aisyah Putri Amanda; Hasbi Miftah Faridz, Melda Julianti Kiswanto, Acim Heri Iswanto (Jurnal Kesehatan, 2024)
Optimal service at the Emergency Department (ED) is crucial considering that every action must be effective and efficient in line with the philosophy of "Time Saving it's Life Saving". However, issues such as long waiting times, inefficient patient flow, and lack of coordination among medical teams often occur. This research aims to review various studies and best practices implemented in applying Lean Six Sigma at the Emergency Department. The literature review method utilized sources from online databases spanning the period 2020-2024. The research findings indicate that Lean Hospital can significantly reduce patient waiting times and enhance ED service efficiency, exemplified by its implementation at the ED of RSI PKU Muhammadiyah Tegal, which reduced waiting times from 69.9 minutes to 51.5 minutes. This implementation also involved strategies such as adding radiology slots and reserving inpatient beds. In conclusion, the application of Lean Hospital in ED has proven effective in improving service quality and efficiency, as well as enhancing patient satisfaction.